16.9k views
2 votes
If f(x)=4x^2+1 and g(x) =x^2-5 find (f-g)(x)

User Camnesia
by
4.5k points

2 Answers

3 votes

Answer: 5x^2 - 4

a p e x

Step-by-step explanation: Once you take the parenthesis away

If f(x)=4x^2+1 and g(x) =x^2-5 find (f-g)(x)-example-1
User Pat Mustard
by
5.2k points
6 votes

Answer:


\huge\boxed{(f-g)(x)=3x^2+6}

Explanation:


(f-g)(x)=f(x)(x)\\\\\text{substitute}\ f(x)=4x^2+1\ \text{and}\ g(x)=x^2-5\\\\(f-g)(x)=(4x^2+1)-(x^2-5)=4x^2+1-x^2-(-5)=4x^2+1-x^2+5\\\\\text{combine like terms}\\\\(f-g)(x)=(4x^2-x^2)+(1+5)=3x^2+6

User Alan Feekery
by
4.6k points